Impact of Rootstocks and Training Systems on Secondary Metabolites in the Skins and Pulp of Vitis labrusca and Brazilian Hybrid Grapes - Francisco José Domingues Neto; Marco Antonio Tecchio; Silvia Regina Cunha; Harleson Sidney Almeida Monteiro; Ricardo Figueira; Aline Nunes; João Domingos Rodrigues; Elizabeth Orika Ono; Mara Fernandes Moura-Furlan; Giuseppina Pace Pereira Lima (Plants)
Grapes are rich in bioactive compounds, including phenolics and anthocyanins, which exhibit antioxidant properties and offer potential health benefits. The accumulation of these compounds is influenced by agronomic practices, particularly rootstock selection and training systems. This study evaluated the effects of different rootstocks (‘IAC 766 Campinas’ and ‘106-8 Mgt’) and training systems (low and high vertical shoot positioning) on the polyphenolic composition and antioxidant activity in the skins and pulps of Vitis labrusca and Brazilian hybrid grapes. The analyses included total phenolics, total flavonoids, monomeric anthocyanins, and antioxidant activity (DPPH and FRAP assays), as well as the individual polyphenolic profile in grape skins. The results indicated that both rootstock and training system significantly affected the accumulation of bioactive compounds and antioxidant capacity. Grapes trained on high trellises exhibited higher concentrations of bioactive compounds, while those from low trellises showed an enhanced phenolic composition. Among Vitis labrusca varieties, ‘Bordô’ had the highest bioactive compounds, while ‘Isabel’ stood out for specific phenolic acids. In hybrid cultivars, the ‘106-8 Mgt’ rootstock boosted antioxidant compounds, while ‘IAC 766 Campinas’ enhanced flavonoid, anthocyanin, and phenolic acid levels. Malvidin-3-O-glucoside emerged as the predominant anthocyanin. These findings underscore the importance of optimizing rootstock selection and training systems to enhance the phenolic composition and antioxidant potential of grapes.